(untitled) (KONFERENSIYA, 2026)
Since CLIL is increasingly being seen as a substitute for ELT (English Language Teaching), many educators are unsure of what CLIL is and if they should use it. We’ll ask language instructors to think about how to enhance not Emphasize students’ language proficiency and topic knowledge in CLIL instruction in order to foster an inspiring learning environment whose outcomes will be crucial for their future academic pursuits as well as their professional lives